Chemotherapeutic responses in canine lymphoma models after treatment with the CHOP protocol - Ramirez, Dominique, author; Wittenburg, Luke, author (Colorado State University. Libraries, 2016)
In both human and veterinary oncology, multi-drug resistance is a phenomenon where a cancer gains a cyto-protective effect against chemotherapeutics. Resistance is often witnessed when remitted cancers relapse and become untreatable. As an example, canine lymphomas are notorious for relapsing after treatment with the multi-drug CHOP protocol. While canonical drug efflux transporters have been implicated with the chemo-resistance phenotype, there are other transporters which might also contribute. Recent research has demonstrated that exposure to chemotherapeutics results in epigenetic changes to transporter gene expression; this could be a possible route for acquiring the resistance phenotype. What is still unknown, however, is a mechanistic understanding of the chemotherapy-transporter expression relationship. To address this void, we are focusing our research on three questions: 1) What are the temporal fluctuations in transporter expression following exposure to multi-drug regimens? 2) What patterns of epigenetic markers on transporter genes promote altered expression? 3) How does transporter expression correlate to protein levels in chemo-resistant lymphomas? We will address each of these questions using a panel of four chemo-sensitive canine lymphomas as our models, and the CHOP protocol as our drug regimen. We will expose the lymphomas to combinations of the CHOP protocol to mimic short- and long-term treatments, and monitor transporter expression via QT-PCR, and epigenetic changes via ChIP-assays. Additionally, protein levels will be monitored with LC-MS/MS methods to correlate expression with translation. We hypothesize that changes in transporter expression exhibit temporal and drug-dependent patterns.
Keywords: chemoresistance; CHOP protocol; SLC transporters; SLC expression; canine clinical lymphoma